(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
British rule in India have deep impact whether it was on social culture or the economic culture of the country. The colonial period brought an end to the social evils prevailing among Indians. Modern education was being brought by the British rule in the India, because of which the modern scientific knowledge is prevailing in the country. Modern industrial unit were being setup under the colonial rule itself. British rule has positive as well as negative impact on the country. During the British rule extreme poverty prevailed among Indians. The colonial rule ruined the artisans and handicraft handlooms of rural India. Agriculture under the colonial rule is stagnant and did not able to perform well. This paper is totally based on secondary data such as government reports, books, newspaper, official website etc.